2007
DOI: 10.1152/ajpendo.00126.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sleep apnea syndrome on the circadian profile of cortisol in obese men

Abstract: It has been hypothesized that sleep apnea syndrome (SAS) increases hypothalamic-pituitary-adrenal axis activity and, through increased cortisol levels, participates in the pathophysiology of metabolic and cardiovascular complications. We compared the circadian profiles of cortisol in obese men with [obSAS+; apnea-hypopnea index (AHI) >or= 20/h] and without SAS (obSAS-; AHI Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
3
26
3
4
Order By: Relevance
“…Our findings are in line with those of Vgontzas et al [22] who showed increased nightly cortisol concentrations in obese apneic patients as compared with obese controls and a trend to reduced cortisol concentrations after CPAP therapy. In contrast, Dadoun et al [23] found no significant differences in cortisol concentrations between obese OSAS patients and obese controls, which may possibly be because of a small number of participants and a distinctly lower mean AHI as compared with that of our study. Other studies focused at single time points in the morning and found no changes in cortisol concentrations upon CPAP therapy [24][25][26].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are in line with those of Vgontzas et al [22] who showed increased nightly cortisol concentrations in obese apneic patients as compared with obese controls and a trend to reduced cortisol concentrations after CPAP therapy. In contrast, Dadoun et al [23] found no significant differences in cortisol concentrations between obese OSAS patients and obese controls, which may possibly be because of a small number of participants and a distinctly lower mean AHI as compared with that of our study. Other studies focused at single time points in the morning and found no changes in cortisol concentrations upon CPAP therapy [24][25][26].…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we included a comparatively high number of participants into this study. This gain possibly accounts for the significant differences in cortisol concentrations after CPAP therapy in our study, where other studies showed trends or failed significance [22,23]. As previously shown, small changes in HPA axis activation within the reference range are also considered to be crucial and are known to be related to, for example, the metabolic syndrome [14,37,38].…”
Section: Discussionsupporting
confidence: 60%
“…However, another reported that OSAS was not associated with any change in the level of salivary or plasma cortisol rhythmicity [29]. In the present study, since no statistically significant differences in the serum cortisol concentrations at each time-point were found between healthy subjects, severe OSAS patients and severe OSAS patients treated with CPAP, the mechanism of induction of hPer1 mRNA at 02:00 h in OSAS patients may not be related to the signalling pathway via GRE.…”
Section: Glucocorticoid Signals To the Mammalian Clock Gene Per1contrasting
confidence: 54%
“…Since OSAS causes an increase in sympathetic activity and may increase cortisol levels [9,14], it can be speculated that patients with OSAS are at higher risk of developing CSC than the general population. We found that 22% of our patients with CSC also suffered from OSAS, whereas OSAS is less frequently reported (2-4%) in the general population [15].…”
Section: Discussionmentioning
confidence: 99%